Socially Responsible Investing: A Critical Appraisal - Johnsen, D. Bruce (2003)
This paper makes three important points regarding socially responsible investing. First, the current methodology involving SRI fund divestiture of the securities of firms that engage in socially irresponsible activity often results in unacceptable unintended consequences. Second, in many cases the proper methodolgy for SRI funds may be purposely to include the securities of such firms in the portfolio in an effort to internalize socially irresponsible interfirm spillovers. Finally, that SRI fund managers may be able to bond their performance by organizing as closed-end funds subject to takeover and liquidation if the stated socially responsible objectives are not met.
Keywords: social responsible investing; Shareholder Wealth; portfolio spillovers; ethical externalities